2015
DOI: 10.1080/10590501.2015.1002999
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Meta-Analysis of Outdoor Air Pollution and Risk of Childhood Leukemia

Abstract: Leukemia is the most frequent malignant disease affecting children. To date, the etiology of childhood leukemia remains largely unknown. Few risk factors (genetic susceptibility, infections, ionizing radiation, etc.) have been clearly identified, but they appear to explain only a small proportion of cases. Considerably more uncertain is the role of other environmental risk factors, such as indoor and outdoor air pollution. We sought to summarize and quantify the association between traffic-related air pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 77 publications
2
84
1
4
Order By: Relevance
“…No evidence of an association between traffic related pollutants and leukaemia was found in a recent Italian study [12]. 13 Among studies that investigated leukaemia by age groups, those that found positive associations with traffic related pollution in all children -consistent with our study -found stronger associations in the age group 0-4 years [10,28]. However, studies that found no evidence of association for leukaemia in all children found no such evidence in young children if these were investigated [12,31].…”
Section: Main Findingscontrasting
confidence: 35%
See 1 more Smart Citation
“…No evidence of an association between traffic related pollutants and leukaemia was found in a recent Italian study [12]. 13 Among studies that investigated leukaemia by age groups, those that found positive associations with traffic related pollution in all children -consistent with our study -found stronger associations in the age group 0-4 years [10,28]. However, studies that found no evidence of association for leukaemia in all children found no such evidence in young children if these were investigated [12,31].…”
Section: Main Findingscontrasting
confidence: 35%
“…A recent review and meta-analysis of previous studies on traffic related pollution and childhood leukaemia suggests increased risks with exposure at diagnosis or longest place of residence, but not with exposure at birth [13]. However, there was evidence of publication bias.…”
Section: Introductionmentioning
confidence: 95%
“…59, 60 Associations were observed for ambient exposures early in life and, to a lesser extent, before birth. The independent contribution of particulate matter (PM10) has been suggested in the development of leukemia.…”
Section: Outdoor Air Pollutionmentioning
confidence: 94%
“…This has thus resulted in the utilization of different biomarkers to assess the pathogenic and health impact of environmental pollution (Briggs, 2003). Some of the health problems associated with exposure to these pollutants include immunosuppression; increase the incidence of disease, reduced life expectancy, reproductive loss and cancers (Filippini et al, 2015). Aside the many global health impacts of environmental pollution, different meta-analysis and systematic review of evidence-based studies have also shown the correlation and association between cancer risk (and prevalence) and diverse environmental risk factors.…”
Section: Introductionmentioning
confidence: 99%